Isolation and in silico analysis of a new subclass of parasporin 4 from Bacillus thuringiensis coreanensis - Santos, Thais N.F. [UNESP]; Moreira, Raquel O. [UNESP]; Rodrigues, Jardel D.B. [UNESP]; Rojas, Luis A.C. [UNESP]; Souza, Jackson A.M. [UNESP]; Desidério, Janete A. [UNESP] (PeerJ, 2025)
Background: Bacillus thuringiensis (Bt) is a Gram-positive bacterium whose strains have been studied mainly for the control of insect pests, due to the insecticidal capacity of its Cry and Vip proteins. However, recent studies indicate the presence of other proteins with no known insecticidal action. These proteins denominated “parasporins” (PS) have cytotoxic activity and are divided into six classes, namely PS1, PS2, PS3, PS4, PS5, and PS6. Among these, parasporins 4 (PS4) has only one described subclass, present in the Bacillus thuringiensis shandongiensis strain. Given the importance and limited knowledge about the actions of PS4 proteins and the existence of only one described subclass, the present work aimed to characterize the Bacillus thuringiensis coreanensis strain as a potential source of PS4 protein. Methods: A preliminary screening to detect the ps4 gene was conducted in a bank of standard strains and isolates of Bacillus thuringiensis from the Laboratory of Bacterial Genetics and Applied Biotechnology, FCAV/UNESP. The positive strain for this gene had its genomic DNA extracted, the ps4 gene was isolated, cloned and in silico analyses of its sequence were performed. Tools such as Bioedit, BLAST, Clustal Omega, Geneious, IQ-Tree, and iTOL were used in these analyses. For the structural analysis of the PS4 detected, in comparison to the database PS4 (BAD22577), the tools Alphafold2, Pymol, and InterPro were used. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gel analyses allowed the visualization of the inactive and active PS4 protein from the positive strain, after solubilization and activation with Proteinase K. Results: Previous screening of Bt standard strains revealed the presence of a partial ps4 gene in Bacillus thuringiensis coreanensis strain. The alignment obtained by the BLAST tool revealed 100% identity between the fragment detected in this work with a hypothetical protein (ANN35810.1) from the genome of that same strain. Considering this, the isolation of the complete gene present in this strain was performed by applying the polymer chain reaction (PCR) technique, using the hypothetical sequence as a basis for the primers elaboration. The in silico analysis of the obtained sequence revealed 92.03% similarity with the ps4 sequence presented in the database (AB180980). Protein modeling studies and comparison of their structures revealed that the B. thuringiensis coreanensis has a new subclass of PS4, denominated PS4Ab1, being an important source of parasporin to be explored in biotechnological applications.
Keywords: Antitumor activity; Bacillus thuringiensis; Bioinformatics; Cancer; Cry; Cytotoxicity; Modeling; Parasporin; Phylogenetics; Pore former